Expanding the Pianist’s Toolbox: Approaches to Arpeggiation, Pedalling, and Gesture - Caravaca González, Óscar (Revista Vórtex, 2025)
This article examines less conventional approaches in piano performance and their potential to expand the performer’s creative space through techniques such as arpeggiation, rhythmic asynchrony, body language communication, and experimental pedalling—all drawn from historical performance practices. Using Schubert’s piano works as a foundation, the study integrates insights from historical treatises, the author’s critical commentary, and practical experimentation, with key findings illustrated through video demonstrations. In exploring alternatives to conventional music performance paradigms, the article articulates a historically informed perspective that foregrounds creative agency and encourages performers to develop their creative voices through expanded interpretive possibilities.